Metabolic and ionic requirements for the intra-axonal transport of noradrenaline in the cat hypogastric nerve - Kirpekar, S. M. (1973)
1. Metabolic and ionic requirements for the intra-axonal transport of noradrenaline were investigated in the cat hypogastric nerve in vitro using a histochemical fluorescence procedure. 2. Specific noradrenaline fluorescence appeared at the proximal region after crushing the nerve at a distance of about 1·5 cm distal to the inferior mesenteric ganglion within 30 min, and the intensity of fluorescence increased with the perfusion time. 3. Prior removal of the ganglion from the rest of the hypogastric nerve, or denervation of the ganglion, had no effect on the appearance of the specific fluorescence. 4. Iodoacetic acid (5 × 10(-4) M), glucose deprivation, dinitrophenol (DNP, 5 × 10(-4) M) and anoxia, singly, did not affect the accumulation of noradrenaline, but combined treatment with glucose deprivation and anoxia, or glucose deprivation and dinitrophenol, very markedly interfered with noradrenaline accumulation. 5. If the temperature of the perfusion fluid was reduced to 15° C, the fluorescence was not seen at the region of occlusion. 6. Removal of sodium from Krebs solution markedly inhibited the axoplasmic transport of noradrenaline. 7. Treatment with ouabain (10(-4) M) or tetracaine (2 × 10(-4) M) did not affect the appearance of specific fluorescence after occlusion. 8. Our findings suggest that transport of noradrenaline storage particles within the hypogastric nerve is dependent on metabolic energy derived from either glycolysis or oxidative phosphorylation. This active process also has an absolute requirement for extracellular sodium ions.